A perceptual dialectological approach to linguistic variation and spatial analysis of Kurdish varieties. Issue 2 (October 2017) - Eppler, Eva; Benedikt, Josef
Abstract : This paper presents the results of the first investigation into Kurdish linguistic varieties and their spatial distribution. Kurdish dialects are used across five nation states in the Middle East and only one dialect, Sorani, has official status in one of these nation states. The study employs the "draw-a-map" task established in Perceptual Dialectology; the analysis is supported by Geographical Information Systems (GIS). The results show that, despite the geolinguistic and geopolitical situation, Kurdish respondents have good knowledge of the main varieties of their language (Kurmanji, Sorani, and the related variety Zazaki) and where to localize them. Awareness of the more diverse Southern Kurdish varieties is less definitive. This indicates that the Kurdish language plays a role in identity formation, but also that smaller isolated varieties are not only endangered in terms of speakers, but also in terms of their representations in Kurds' mental maps of the linguistic landscape they live in.